The Meaning of the Principal's Humanistic-Spiritual Servant Leadership in School Governance at SDN 1 Manukaya - Putu Gita Gauri Sugiartana; Ni Ketut Desia Tristiantari; Gusti Ayu Putu Sukma; I Gusti Ayu Agung Deva Wahyu Wulandari; Ni Luh Ika Sulastri Anjani (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to understand the meaning of the principal’s humanistic-spiritual servant leadership at SD N 1 Manukaya through a phenomenological approach. This research employed a qualitative method using interviews, observations, and documentation. The informants consisted of the principal and two teachers.The results showed that humanistic-spiritual servant leadership is interpreted as leadership oriented toward service, empathy, open communication, and family-like relationships within the school environment. The leadership practice also contains spiritual values such as sincerity, moral responsibility, and devotion to others, which are relevant to the concept of Manava Seva Madhava Seva. This study indicates that humanistic-spiritual servant leadership is able to build a harmonious and humanistic school culture at SD N 1 Manukaya.